1964
DOI: 10.3382/ps.0431086
|View full text |Cite
|
Sign up to set email alerts
|

The Growth and Composition of Skeletal Muscle in the Chicken

Abstract: The relationship between the weight of the breast muscle and the number of nuclei

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
10
0

Year Published

1965
1965
1989
1989

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 4 publications
2
10
0
Order By: Relevance
“…Our results (Table 1) confirm the earlier observations in several different strains of growing chickens (Moss et al, 1964;Mizuno and Hikami, 1971;MacDonald and Swick, 1981). The developmental decrease in the concentration of nucleic acids and the increase in the DNA-unit size have been observed in the skeletal muscles of other strains of chicken as well (Mizuno and Hikami, 1971;Knitzetova et al, 1972;Cornejo et al, 1980).…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Our results (Table 1) confirm the earlier observations in several different strains of growing chickens (Moss et al, 1964;Mizuno and Hikami, 1971;MacDonald and Swick, 1981). The developmental decrease in the concentration of nucleic acids and the increase in the DNA-unit size have been observed in the skeletal muscles of other strains of chicken as well (Mizuno and Hikami, 1971;Knitzetova et al, 1972;Cornejo et al, 1980).…”
Section: Discussionsupporting
confidence: 95%
“…In very young chicks, no significant differences in total DNA or nuclei in a whole muscle exists between slow-growing and fast-growing strains (Moss et al, 1964;Mizuno and Hikami, 1971). As age advances, however, total DNA in fast-growing chicks increases at a faster rate (Table 1) than in slow-growing birds.…”
Section: Discussionmentioning
confidence: 88%
“…A difference in the cytoplasm per nucleus in multinucleated muscle cells could mean either differentially hypertrophied fibers, with a constant nuclei number or a differential rate of nuclei formation during growth. Moss (16) postulated that in chickens the cytoplasm per nucleus was constant throughout posthatching growth, while Robinson ( 17) showed in pigs, and Winnick and Noble (18) in rats, an increasing ratio of cytoplasm per nucleus during early growth indicating a relatively greater rise in cytoplasmic constituents relative to DNA as growth proceeded. Table I presents the DNA, RNA, and protein concentrations of biopsies from 3 animals of each genotype.…”
mentioning
confidence: 97%
“…DNA has been used, therefore, as a reference substance against which to measure changes in other cytoplasmic constituents and also as a measure of the number of nuclei present in a given organ and tissue. Total wet weight of the muscle divided by the total DNA content provides an index of cytoplasm/nucleus, since the DNA content per nucleus is constant a t 2.5 X mg (16). The "cytoplasm per nucleus" provides an index of the cell numbers and cell size and, when measured during growth, an index of the rate of cellular hyperplasia and hypertrophy.…”
mentioning
confidence: 99%
“…While this experiment was in progress, Moss et al 6), working with the chicks of three breeds, reported that the number of nuclei of the skeletal muscle, which was computed from the content of deoxyribonucleic acid (DNA) in the muscle, increased 13-to 20-fold from hatching to 24 days of age. In agreement with Moss et al, we also observed a steady increase in DNA content of the skeletal muscle in the growing chicks.…”
mentioning
confidence: 99%